THE INFLUENCE OF E-GOVERNMENT IMPLEMENTATION ON SERVICE QUALITY AT THE UPTD PUSKESMAS AMPAH, DUSUN TENGAH DISTRICT - Ahmad Nabhan; Akhmad Berkatillah; Hasbi Salim (Journal of Development Administrations Thinking Understand: Public and Business Administration (DATU), 2026)
The implementation of a digital system at the Ampah Community Health Center (Puskesmas), as mandated by Law No. 17 of 2023, is primarily aimed at modernizing services. However, the reality on the ground remains hampered by inadequate human resource readiness and unstable electricity infrastructure. This associative quantitative research aims to examine the impact of e-Government implementation on public service performance. Ninety-six respondents were analyzed using the Partial Least Square (PLS) method. Based on hypothesis testing, empirical evidence was found that the e-government system had a positive and significant impact, contributing 55.5% to improving service quality. This figure validates Indrajit and Tjiptono's theory, although the study acknowledges limitations due to its failure to include other complex variables such as user digital literacy. To address the identified operational challenges, strategic recommendations focus on intensifying outreach and staff competency training to ensure optimal system performance. This synergy between technical improvements and active citizen participation is a crucial foundation for realizing adaptive, transparent, and efficient public health governance in East Barito Regency.